The anti-arch inhibition effect of multispan continuous girder bridge strengthened with prestressed CFRP plates. (January 2022) - Wu, Bitao; Zhou, Yujian; Yin, Xiang; Lin, Zucai; Zhou, Zhenwei
Abstract: To study the interactions of longitudinal deformations on multispan continuous girder bridges strengthened with the prestressed Carbon fiber reinforced polymer (CFRP) plates, the reinforcement mechanism, and the stress distribution of bridges are analyzed. Then, a refined three-dimensional numerical model of continuous girder bridge strengthened with prestressed CFRP plates is established to study the influence of the number of adjacent spans on the reinforcement effect. The study shows that there is an "anti-arch inhibition effect" when multispan continuous girder bridges are strengthened with prestressed CFRP plates. Finally, to assess the "anti-arch inhibition effect", the tension prestress of a continuous girder bridge strengthened with prestressed CFRP plates is optimized so that each span of a multispan continuous girder bridge can achieve a balanced reinforcement effect. The results show that the interaction between adjacent spans should be considered, and the ultimate reinforcement effect of the full-bridge is not optimal when the tensile prestress of the CFRP plate is the same for each span. By optimizing the prestressed ratio of the CFRP plates, the reinforcement effect can be optimized, the adverse effects of adjacent spans can be reduced, and the utilization rate of CFRP reinforcement can be improved.